Penerapan Pembelajaran Matematika Realistik Untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa Pada Materi Bentuk Aljabar di Kelas VII SMP - Sinaga, Nurvitri (Unika Santo Thomas Medan, 2018)
This study aims to determine the level of mathematical understanding ability of students before and after the application of realistic mathematics learning and to describe the application of the Realistic Mathematics Learning approach at Nempu Hilir State Middle School 3 in the algebraic material form. This type of research is Classroom Action Research. The research subjects were seventh grade students of State Junior High School 3 Siempat, Nempu Hilir 2017/2018 Academic Year, amounting to 30 people. The results of this study indicate that the level of mathematical understanding of students in class VII-C State Junior High School 3 Siempat Nempu Hilir before and after the application of Realistic Mathematics Learning increased. The application of realistic mathematical learning approaches is applied in several steps, namely first, providing contextual problems. Second, explain contextual problems. Third, resolve contextual problems. Fourth, discuss answers. Fifth, conclude. The implementation of a realistic mathematics learning approach in the State Junior High School 3 Siempat of Nempu Hilir in the algebraic form material has been classified as good.